Persepsi Mahasiswa Indonesia di King Saud University Riyadh terhadap Makna Bid’ah dan Implikasinya pada Praktik Keagamaan - Syahri Ramadhan Siregar; Nasrulloh Nasrulloh; Ahmad Mukhlis Siregar (Sujud: Jurnal Agama, Sosial dan Budaya, 2026)
This study aims to identify Indonesian students’ perceptions at King Saud University Riyadh regarding the concept of bid‘ah and analyze its implications for daily religious practices. The study employed a descriptive quantitative approach using an exploratory survey design. Data were collected through an online Likert-scale questionnaire distributed to Indonesian students at King Saud University Riyadh. Out of a population of 29 students, 21 respondents completed the questionnaire and were included in the analysis. The data were analyzed using descriptive statistics, including frequencies, percentages, and response tendencies. The findings reveal that students’ understanding of bid‘ah is dynamic and cannot be categorized as entirely textual or contextual. While some respondents emphasized strict adherence to the Prophet’s Sunnah, most still accepted the concept of bid‘ah hasanah and continued participating in religious practices such as tahlilan, mawlid celebrations, yasinan, and collective dhikr. The study indicates that theological understanding of bid‘ah does not necessarily lead to direct changes in religious practices. Theoretically, this study contributes to empirical discussions on the reception of bid‘ah within the context of the Indonesian Muslim diaspora, while methodologically highlighting the importance of descriptive empirical approaches in contemporary socio-religious studies.